Complete implementation of the combined TEG-TEC temperature control and energy harvesting system. (February 2020) - Kwan, Trevor Hocksun; Wu, Xiaofeng; Yao, Qinghe
Abstract: Previously, the combined thermoelectric generator and cooler (TEG-TEC) control technique was proposed for thermal management of devices, where the TEG mode is used for energy harvesting and the TEC mode is used for active temperature control. This research significantly improves the TEG-TEC control technique by including the components that ensure the TEG output power can truly be returned to the original power source. Specifically, two cascaded boost converters are adopted in the TEG power circuit where the former is used to achieve maximum power point tracking, and the latter provides an additional constant voltage gain to improve the circuit's compatibility. Both a Simscape based simulation model and the modified experimental platform involving a lithium ion battery is used to demonstrate the improved implementation. Moreover, for the sake of demonstration, two control algorithms, namely the basic nested IF loop and a fuzzy logic controller, are adopted and their performances are compared. Finally, a steady state analysis of the Simscape model involving a parametric sweep of the input waste heat shows that the TEG mode can only be engaged for a certain range. Highlights: The combined thermoelectric generator – cooler control design is completed. A Simscape model and experimental hardware are used to demonstrate the new design. Power via the TEG mode is recovered by the common lithium ion battery. The new design involves two cascaded boost converters for the TEG mode. The experimental platform showed 58.7% energy harvesting efficiency via TEG mode.